The potential role of Epstein-Barr Virus in breast cancer development: Role of epstein-barr virus in breast cancer - Gouadfel, Kahina; Khenchouche, Abdelhalim; Rabea, Sameh; Mansour, Ahd A.; Salem-Bekhit, Mounir M.; Ouhida, Soraya; Msela, Amine; Salem, Mohamed M.; Erto, Alessandro; Benguerba, Yacine; Houali, Karim (Cellular and Molecular Biology, 2023)
We are looking into viral components that may contribute to breast cancer in order to find possible therapeutic targets. The Epstein-Barr virus (EBV), which has been found to cause nasopharyngeal carcinoma and Burkitt lymphoma, is thought to play a role in breast cancer. Our series’ patients had a median age of 49, with nearly half being under the age of 49. T2 tumors (two to five centimeters in size) make up the vast majority of our collection (60%). Six percent of our patients showed lymph node involvement, with roughly the same number in the N1 and N2 stages (41.17% each). Only 17.64% of people are at the N3 stage. SBR II tumors were the most common (90%). Only 20% of patients have HER2 overexpression, whereas 73.33% have ER expression. EBV was found in 23.33% of breast carcinomas (7 cases/30) after oncoprotein LMP1 expression, but normal surrounding tissues tested negative. We discovered that overexpression of the HER2 protein is inversely related to the two HRs’ expression. They have no relationship with EBV infection and, consequently, LMP1 expression. LMP1 expression was not shown to be linked with patient age, tumor grade, tumor size, or lymph node invasion.